Anthropometric characteristics and risk of lymphoid and myeloid leukemia in the European Prospective Investigation into Cancer and Nutrition (EPIC). - Saberi Hosnijeh, F; Romieu, I; Gallo, V; Riboli, E; Tjønneland, A; Halkjær, J; Fagherazzi, G; Clavel-Chapelon, F; Dossus, L; Lukanova, A; Kaaks, R; Trichopoulou, A; et al. (2013)
PURPOSE: Overweight and obesity have been suggested as a risk factor for leukemia. Impaired immune function associated with obesity, increased insulin-like growth factor-I activity and stimulating effects of leptin suggest a possible biological link between anthropometric measures and leukemia. However, evidence from epidemiological studies has been inconsistent. We examined the potential association between prospective measurements of body size and risk of leukemia among participants of the European Prospective Investigation into Cancer and Nutrition (EPIC). METHODS: During follow-up (mean = 11.52 years, standard deviation = 2.63), 671 leukemia (lymphoid leukemia = 50.1 %, myeloid leukemia = 43.2 %) cases were identified. Anthropometric measures including weight, height, body mass index (BMI), waist circumference (WC), hip circumference, and waist-to-hip ratio (WHR) were measured. Cox proportional hazard models were used to explore the association between anthropometric measures and risk of leukemia. RESULTS: No associations were observed between anthropometric measures and total leukemia, and lymphoid leukemia. Risk of myeloid leukemia significantly increased for higher categories of BMI and WC among women. Analyses by subtype of myeloid leukemia showed an increased risk of acute myeloid leukemia (AML) for higher categories of WHR among women. This association seemed to be reversed for chronic myeloid leukemia. No association between anthropometric measures and myeloid leukemia were observed among men except an increased risk of AML with height. CONCLUSION: The study showed no associations between anthropometric measures and total leukemia, and lymphoid leukemia among men and women. A possible association between BMI as general obesity and WC as abdominal obesity and increased risk of myeloid leukemia among women were observed.